2012
DOI: 10.1159/000340057
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mass and Obesity-Associated Gene (<b><i>FTO</i></b>) in Eating Disorders: Evidence for Association of the rs9939609 Obesity Risk Allele with Bulimia nervosa and Anorexia nervosa

Abstract: Objective: The common single nucleotide polymorphism (SNP) rs9939609 in the fat mass and obesity-associated gene (FTO) is associated with obesity. As genetic variants associated with weight regulation might also be implicated in the etiology of eating disorders, we evaluated whether SNP rs9939609 is associated with bulimia nervosa (BN) and anorexia nervosa (AN). Methods: Association of rs9939609 with BN and AN was assessed in 689 patients with AN, 477 patients with BN, 984 healthy non-population-based controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 78 publications
0
32
0
Order By: Relevance
“…Only two SNPs, rs1523921 (also found to be suggestively associated in the main case-control analysis) and rs10777211 located 333kb upstream of ATP2B1 , showed association at the 10 -5 significance level (Table S6). Similarly, subsequent analyses pertaining to associated phenotypes (weight regulation: BMI/obesity loci, 40, 61, 69, 70 and loci for extreme obesity; 61, 71, 72 psychiatric comorbidities: ADHD, schizophrenia, bipolar disorder, and major depressive disorder) or previous equivocal association findings for AN or eating disorders (AN variants, 42 eating disorder related symptoms, behaviors, and personality traits variants 59, 60 ) did not reveal significant findings. More adequately powered analyses that could allow us to detect variants that can distinguish between these two subtypes could be clinically meaningful in predicting clinical course and outcome and eventually in designing targeted therapeutics.…”
Section: Discussionmentioning
confidence: 91%
“…Only two SNPs, rs1523921 (also found to be suggestively associated in the main case-control analysis) and rs10777211 located 333kb upstream of ATP2B1 , showed association at the 10 -5 significance level (Table S6). Similarly, subsequent analyses pertaining to associated phenotypes (weight regulation: BMI/obesity loci, 40, 61, 69, 70 and loci for extreme obesity; 61, 71, 72 psychiatric comorbidities: ADHD, schizophrenia, bipolar disorder, and major depressive disorder) or previous equivocal association findings for AN or eating disorders (AN variants, 42 eating disorder related symptoms, behaviors, and personality traits variants 59, 60 ) did not reveal significant findings. More adequately powered analyses that could allow us to detect variants that can distinguish between these two subtypes could be clinically meaningful in predicting clinical course and outcome and eventually in designing targeted therapeutics.…”
Section: Discussionmentioning
confidence: 91%
“…154 As mentioned in the linkage section, preliminary results involving the OPRD1 gene have been reported in AN, 66,67 whereas opioid receptor mu 1 gene ( OPRM1 ) has been implicated in hedonic eating in one study with 300 participants. 155 The fat mass and obesity-associated gene ( FTO ), which has been identified as an obesity locus in multiple GWAS publications, 156,157 has yielded mixed findings regarding a possible association with AN or BN, 127,158,159 and studies have yet to be conducted on its possible role in BED. Thus far, the most comprehensive candidate gene study of AN has investigated the role of 182 genes in 1,085 AN cases and 677 healthy controls, in which none of the markers reached statistical significance following correction.…”
Section: Molecular Genetic Studies Of Eating Disordersmentioning
confidence: 99%
“…Indeed, we and others have shown that variability in these genes is also associated with ED‐related behaviors (Gamero‐Villarroel et al., 2014, 2015; Muller et al., 2012; Rybakowski et al., 2007). According to this background, we hypothesized in the present work that TFAP2B and KCTD15 variants, either isolated or in combination, may influence personality dimensions in anorexia nervosa (AN) or bulimia nervosa (BN) patients.…”
Section: Introductionmentioning
confidence: 99%